2016
DOI: 10.1038/srep24370
|View full text |Cite
|
Sign up to set email alerts
|

Rolling-induced Face Centered Cubic Titanium in Hexagonal Close Packed Titanium at Room Temperature

Abstract: Combining transmission electron microscopes and density functional theory calculations, we report the nucleation and growth mechanisms of room temperature rolling induced face-centered cubic titanium (fcc-Ti) in polycrystalline hexagonal close packed titanium (hcp-Ti). Fcc-Ti and hcp-Ti take the orientation relation: 〈0001〉hcp||〈001〉fcc and , different from the conventional one. The nucleation of fcc-Ti is accomplished via pure-shuffle mechanism with a minimum stable thickness of three atomic layers, and the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 36 publications
5
50
2
Order By: Relevance
“…It was reported that the α (hcp) to ω (hcp) and α (hcp) to fcc phase transformation can accommodate macro-strains comparable to compression twins in Ti [10] but it is important to note that an α (hcp) to ω (hcp) phase transformation was not observed in this research.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…It was reported that the α (hcp) to ω (hcp) and α (hcp) to fcc phase transformation can accommodate macro-strains comparable to compression twins in Ti [10] but it is important to note that an α (hcp) to ω (hcp) phase transformation was not observed in this research.…”
Section: Discussionmentioning
confidence: 48%
“…Basically, the formation of the fcc phase is not anticipated from the equilibrium phase diagram of Ti [4], but there are experiments showing an fcc structure in very thin epitaxial films [5,6] and in high-energy milled powders [7,8]. Very recently, an hcp to fcc phase transformation was reported in a bulk commercial purity α-Ti during cryogenic channel die compression [9] and cold rolling [10].…”
Section: Introductionmentioning
confidence: 99%
“…An example of the drag effect is the formation energy, activation energy for motion, and general kinetics of kink nucleation and propagation at disconnections. Kinks and kink motion have been observed on disconnections [46,249]. However the 3D, non-periodic nature of kinks makes the calculation of their energetics difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the surface mesh has been formed due to the occurrence of BCC to FCC phase transformation during the cryo‐rolling process (shown in Figure ). Literature studies have also shown the occurrence of phase transformation in various metallic systems during the rolling process, and it is to be noted that such transformations aid in the plastic deformation of the specimen at low temperatures. In the present case, it is observed that the BCC to FCC phase transformation occurs only near the roller‐specimen interface and as the specimen moves forward along the rolling direction (Figure c), the transformed region (FCC) regains its original BCC phase.…”
Section: Resultsmentioning
confidence: 99%